Моделювання радiацiйних та релаксацiйних процесiв в iмплантованих iонами кисню плiвках залiзоiтрiєвого гранату - Остафійчук, Б.К.; Ткачук, В.М.; Ткачук, О.М.; Пилипiв, В.М.; Григорук, О.О. (Видавничий дім "Академперіодика" НАН України, 2008)
The mechanisms of the formation of defects in superficial layers of epitaxial yttrium iron garnet films during the implantation by oxygen ions (E = 90 keV) are investigated by mathematical modeling methods. Secondary implantation processes and the evolution of the cascade collisions of target atoms up to a thermodynamical equilibrium state are studied.